[Review into the risks of fraud and corruption in local government procurement : A commitment from the UK Anti-Corruption Strategy 2017-2022].: A commitment from the UK Anti-Corruption Strategy 2017-2022]. Fraud and Corruption Case Studies Sent in by Councils. [Annex 4], (2020) - Unknown
No abstract available